وحدة مقترحة في التغيرات المناخية قائمة على التعليم المدمج بمنهج العلوم للمرحلة الابتدائية لتنمية الوعي بالمتغيرات المناخية - عبدالقادر، رحاب جمال الدين شلبي (جامعة بنها - كلية التربية, 2023)
استهدف البحث الحالي إعداد وحدة مقترحة في التغيرات المناخية قائمة على التعليم المدمج بمنهج العلوم للمرحلة الابتدائية لتنمية الوعي بالتغيرات المناخية، ولتحقيق ذلك تم بناء الوحدة "التغيرات المناخية: مسبباتها ومخاطرها" في ضوء التعليم المدمج، وتم إعداد الاختبار المعرفي للوعي بالتغيرات المناخية، ومقياس الاتجاه نحو قضايا المناخ ومخاطرها، وتم تطبيقهما قبليا وبعديا على مجموعة البحث التجريبية والتي تكونت من (٣٥) تلميذا وتلميذة من تلاميذ الصف السادس الابتدائي، وتوصلت نتائج البحث إلى: * وجود فرق ذو دلالة إحصائية عند مستوى دلالة (α ≤ 0.05) بين متوسطي درجات المجموعة التجريبية لتلاميذ الصف السادس الابتدائي لصالح التطبيق البعدي للاختبار المعرفي للوعي بالتغيرات المناخية. * وجود فرق ذو دلالة إحصائية عند مستوى دلالة (α ≤ 0.05) بين متوسطي درجات المجموعة التجريبية لتلاميذ الصف السادس الابتدائي لصالح التطبيق البعدي المقياس الاتجاه نحو التغيرات المناخية لصالح التطبيق البعدي. The current research aimed to prepare a climate changes unit based on blended learning in the primary stage science curriculum for developing awareness of climate changes. To achieve this, the unit "Climate Changes: Their causes " was built in the light of blended learning. A cognitive climate changes awareness test was also prepared. Besides, an attitude scale towards climate Changes was also designed. Both the test and the scale were pre-post applied to the experimental research group, which consisted of (35) male and female from the sixth primary grade pupils. Results of the research revealed that: * There is a statistically significant difference at the significance level (α ≤ 0.05) between the mean scores of the experimental group for sixth-grade primary school pupils in favor of the post-application of the cognitive climate changes awareness test. * There is a statistically significant difference at the level of significance (α ≤ 0.05) between the mean scores of the experimental group for sixth-grade primary school pupils in favor of the post-application of the attitude scale towards Changes, in favor of the post-application.
Keywords: التغيرات المناخية -- النظام البيئي -- العملية التعليمية -- مادة العلوم -- المرحلة الابتدائية